WILAYAH POTENSIAL DALAM PENGEMBANGAN AGROWISATA BUAH DI KABUPATEN CIREBON - Nur Syamsiyah; Sulistyodewi Sulistyodewi; Tuti Karyani (Universitas Tribhuwana Tunggadewi, 2017)
Agriculture in Cirebon Regency very developed, one of the production of agricultural products that have increased the commodity of fruits, in addition to the agricultural sector, the tourism sector became the attraction of visitors to visit Cirebon regency. To be able develop agro-tourism potential areas that will be used as an area of agrobased development of fruit plants such as mango, guava, papaya and banana. Potential superior commodity areas were analyzed using Location Quotient (LQ) analysis of several subdistricts in Cirebon Regency. Cirebon Regency consists of 40 sub-districts, from 40 sub-districts there are 7 districts that become the commodity fruits base sector with LQ value above 1. Subdistricts that become the base areas are Sedong Subdistrict, Susukan Lebak Subdistrict, Greged Subdistrict and Duku putang Subdistrict The base area for the mango fruit commodity, Jamblang District as a guava commodity development area, Duku Puntang subdistrict and Greged sub district is the base for papaya commodities, and Lemah abang and Susukan subdistricts are the basis of banana commodities. For Localization Coefficient and Specialization coefficient, in sub-districts which are fruit commodity base sector there is not one subdistricts which is centered in producing a commodity or specializing in certain farming activities.